Role of mechanization: The impact of the cropland use scale on fertilizer reduction - Liu, Jin; Xu, Qing; Zhou, Tianshu (Frontiers in Environmental Science, 2022)
The input of chemical fertilizer to save land and the input of agricultural mechanization to save labor have been important driving forces for China’s grain production since the reform and opening-up. In recent years, the existing literature discussed the relationship between the scale of agricultural land and the application of chemical fertilizer but ignored the role of mechanization on agricultural production and management. We used the intermediary effect model to examine how the cropland use scale affected farmers’ fertilization behavior through agricultural mechanization investment. Our dataset contained data from Fixed Observation Points of the Ministry of Agriculture and Rural Affairs in China conducted between 2015 and 2017. The results showed that the expansion of cropland scale significantly reduced the fertilizer input per mu, and indirectly reduced the fertilizer input of farmers by increasing the input of agricultural mechanization. In a word, agricultural mechanization played a mediation effect. The further heterogeneity results showed that because grain crops are easier to operate mechanically, the mediation effect was more significant; Similarly, under the patterns of ‘South prefer to service, north prefer to self-purchase’ and ‘South grow rice and north grow wheat’, southern areas received more significant reduction effect in mainland China. These findings defined the role of agricultural mechanization and provided a new perspective for realizing the reduction and efficiency of chemical fertilizer and reducing agricultural non-point source pollution.